The Phenomenon of Eastern Spiritual Practices, and the Problem of its Sociological Conceptualization - Zubarev, Alexander (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
The phenomenon of Eastern spiritual practices is considered in the article. The problem of its sociological conceptualization is solved in the paper. The author appeals to the works of Jung K.-G., Fromm E., Abaev N., Torchinov E., where this phenomenon of culture is studied. The complexity and ambiguity of interpretation of the terms «East» and «spiritual practice» is emphasized. Sociological conceptualization of the phenomenon of the Eastern spiritual practices through the concept of body techniques and the concept of cultural form is proposed